The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1111/aos.12137
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure and corneal biomechanics in Fuchs’ endothelial dystrophy and after posterior lamellar keratoplasty

Abstract: . Purpose:  To evaluate the precision of techniques for measuring intraocular pressure (IOP) in corneas with presumably altered biomechanical properties. Methods:  Intraocular pressure was measured with a Goldmann applanation tonometer (GAT), ocular response analyzer (ORA) and dynamic contour tonometer (DCT) in 70 eyes. Thirty‐five eyes were normal corneas, 18 eyes had Fuchs’ endothelial dystrophy, and 17 eyes had undergone Descemet’s stripping automated endothelial keratoplasty (DSAEK) surgery. Corneal hyster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
23
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 37 publications
4
23
0
5
Order By: Relevance
“…IOP g was almost identical between case and control eyes both pre-and postoperatively, which is in line with the results of a previous study. 10 In the present study, IOP cc yielded the highest pressure values in patients with PBK as well as after DSAEK. This measurement is intended to compensate for biomechanical properties and be less affected by CCT than by GAT in corneas with abnormal thickness.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…IOP g was almost identical between case and control eyes both pre-and postoperatively, which is in line with the results of a previous study. 10 In the present study, IOP cc yielded the highest pressure values in patients with PBK as well as after DSAEK. This measurement is intended to compensate for biomechanical properties and be less affected by CCT than by GAT in corneas with abnormal thickness.…”
Section: Discussionsupporting
confidence: 54%
“…This is in accordance with the results of other studies demonstrating that corneal biomechanical parameters are significantly lower in other causes of corneal edema such as Fuchs endothelial dystrophy. 9,10 This reduced corneal rigidity is attributable to slacking of stromal fibres in the posterior corneal layers because of edema. 12 The results of the present study demonstrated that CH and CRF are significantly improved after DSAEK and become comparable to those of the normal fellow eye.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were reported by Yi et al 15 and Clemmensen and Hjortdal. 29 Yi et al 15 also showed that patients with preexisting glaucoma are much more likely to develop a steroid response after DSEK as compared with unaffected individuals. Lower rates of graft rejection in DSEK 2 could potentially allow earlier tapering of steroids, leading to a lower risk of steroid-induced glaucomatous optic nerve damage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have shown that the increased corneal thickness after DSEK does not significantly influence IOP measurement, making correction of IOP according to corneal thickness unnecessary. 18,19 In a recent retrospective study by Sandhu et al 9 that included 61 eyes with a 12month follow-up, elevated IOP was found to be a serious aftereffect of both PK and DSEK, with at least 30% pressure elevation from baseline within 1 year in 39% of cases. However, given the low number of eyes included and the short follow-up of patients in that study, the similar incidences observed do not necessarily indicate an absence of differences between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%